Predictive Maintenance of Cooling System in Casting Process by Data SCADA - Engelbert Harsandi Erik Suryadarma, The Jin Ai, Brilianta Budi Nugraha (International Journal of Advanced Science and Technology, 2020)
In the casting process, cooling system is very important. Without a good cooling system,the casting process will be very long time and the process of solidification becomesuncontrolled. This paper presents a comprehensive predictive maintenance system for thecooling system of the die casting process. This predictive maintenance system is created inorder to ensure the cooling system remained in good condition throughout the process. Itis built based on the SCADA system combined with data mining technique, which is linearregression algorithm combined with rule based classification. We use prototype of castingprocesses on a laboratory scale in order to test this system.